A restricted nonlinear large eddy simulation model for high Reynolds number flows. Issue 2 (1st February 2018) - Bretheim, Joel U.; Meneveau, Charles; Gayme, Dennice F.
ABSTRACT: Recent numerical studies of the restricted nonlinear (RNL) model have demonstrated its ability to reproduce important features of wall turbulence despite a severe reduction in the number of degrees of freedom. In these prior studies, the RNL model included full resolution of the viscous term. In this work, we extend the RNL model to arbitrarily high Reynolds numbers by developing a RNL large eddy simulation (LES) framework along with a method to systematically identify an appropriate streamwise wavenumber support based on spectral properties of wall turbulence. This method leads to a band-limited RNL–LES system which is successful in reproducing some of the most important statistical features captured in previous low to moderate Reynolds number simulations, e.g. the mean velocity and second-order moment profiles. The RNL–LES framework offers a new approach to understanding the connection between coherent structures and the momentum transfer mechanisms of wall turbulence at arbitrarily high Reynolds numbers, where resolution of the viscous terms can become computationally expensive even with the relatively low computational complexity afforded through the dynamical restriction of the RNL model.